Tuning of Cell-Biomaterial Anchorage for Tissue Regeneration - Leal-Egaña, Aldo; Diaz-Cuenca, Aranzazu; Boccaccini, Aldo R. (Advanced Materials, 2013)
Which mechanisms mediate cell attachment to biomaterials? What role does the surface charge or wettability play on cell-material anchorage? What are the currently investigated strategies to modify cell-matrix adherence spatiotemporally? Considering the development of scaffolds made of biocompatible materials to temporarily replace the structure and/or function of the extracellular matrix, focus is given to the analysis of the specific (i.e., cell adhesive peptide sequences) and unspecific (i.e., surface charge, wettability) mechanisms mediating cell-matrix interactions. Furthermore, because natural tissue regeneration is characterized by the dynamic attachment/detachment of different cell populations, the design of advanced scaffolds for tissue engineering, based in the spatiotemporal tuning of cell-matrix anchorage is discussed. Focus is given on the analysis of the specific and unspecific mechanisms mediating cell-matrix interactions. Furthermore, because natural tissue regeneration is characterized by the dynamic attachment/detachment of different cell populations, the advanced design of scaffolds for tissue engineering, based in the spatiotemporal tuning of cell-matrix anchorage, is discussed. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.tuning
Keywords: cell adhesion; cell-matrix anchorage; spatiotemporal tuning; tissue engineering; tunable biomaterials